Economics of Production and Marketing of Ginger in Kerala with Special Reference to Idukki District - Jayesh KS (Department of Agricultural Economics, College of Horticulture, 1994)
The present study on production and marketing of ginger was undertaken in Idukki district during the year 1992-93. The major objectives of the study were to examine the past trends in production, estimation of cost of cultivation, cost of production, resource use efficiency, marketing cost and margin and to identify the marketing channels. The study also examines the major constraints in production and marketing of ginger. The study is based on primary and secondary data. Primary data is collected from a sample of farmers. Multistage random sampling was adopted for the selection of farmers. Ginger production in the state during the period 1962-63 to 1990-91 showed a rising trend, with productivity contributing significantly to rise in production. In Idukki district also increase in trend in production is recorded during 1978-79 to 1991-92 period. Contarary to what has happened in state area played a major role with productivity playing a complementary role. Average cost of cultivation per hectare of ginger based on cost A, cost B and cost C were Rs.20088.10, Rs.20088.10 and Rs.28888.10 respectively. The average yield of ginger was 13785.08 kg per hectare. The gross value of output at prevailing price rate was Rs.68925.40. Cost of production per tonne of ginger based on cost A, cost B and cost C were Rs.1467.30, Rs.1467.30 and Rs.2119.60 respectively. Input-output ratio based on cost A, cost B and cost C were Rs.3.43, Rs.3.43 and Rs.2.39 respectively. Bulkline cost per tonne of ginger was Rs.2500. Farm business income was Rs.48837.30 and net income was Rs.40037.30. Cobb-Doughlas production function fitted with returns (rupees) as dependant variable and area, expenditure on inputs like seed, chemical fertilizers, manures, plant protection chemicals and human labourer as independent variables revealed that additional expenditure on seed, chemical fertilizers, manures and plant protection chemicals could increase the output. The input human labour was found to be in excess use. The most important marketing channel identified for both green and dry ginger was producer – village merchant – commission agent – wholesaler – retailer/secondary wholesaler – consumer. In the case of dry ginger producer sale price formed 62 per cent of the retail price. The corresponding share in the green ginger trade was 37 per cent. The combined net margin of the intermediaries were 19.6 per cent of the consumer rupee in dry ginger trade while it was 23.3 per cent in green ginger. The major problems facing the ginger growers are instability in prices and loss due to softrot disease. The study suggest the formation of co-operative societies to arrest price fluctuations. The study also recommend to educate farmers in modern techniques of cultivation.